"Making the Connection": Aggregate Internship Data as Direct and Indirect Measure Informing Curricula and Assessment. (March 2019) - Bugeja, Michael; Garrett, Melissa
This article focuses on aggregate internship data from an accredited Midwestern mass communications school to illustrate how feedback loops inform curricula and assessment according to standards of the Accrediting Council on Education in Journalism and Mass Communications (ACEJMC). A sample survey instrument is shared with data directly related to ACEJMC values and competencies. Final recommendations are made to help accredited programs earn compliance in assessment by using direct and indirect measures from internships.